THE PROCESS OF INDONESIAN NATION STATE FORMATION, 1901-1998 (History Department, Semarang State University and Historian Society of Indonesia, 2018)
This article has analyzed the long process of Indonesian Nation State Formation, namely from the Dutch Colonial Period to New Order Era of the 1980s and 1990s. The article argues that the concept of nationhood remained very fluid for long time but gradually it started to shape after the introduction of western education to the natives in the Dutch Colonial era and it took the final shape in New Order Era. The complexity of the nation-state formation was due to the region consists of many ethnics, cultures, languages, religions, and political parties. Their national identity started from the ethnicity awareness which took shape in the Dutch Colonial Era. During the Japanese occupation era the Nation State Formation of Indonesia was put into action as Kurasawa said that they had been prepared the independence of Indonesian nation. In Sukarno era, Indonesia was still ideologically divided into some international ideologies such as Communism, Islamism, and the secular national ideology. The peak of the rivals is the breaking of Indonesian Communist Party uprising in 1965. A major change took place with the fall of Sukarno’s regime which was replaced by General Suharto. Suharto called the Sukarno era as the old order regime and called his regime as New Order. The stability of Indonesian National formation was restored with ban on the International Ideology such as Communism, forcing the Moslem militancy and using National Ideology (Pancasila) as the ones of National Ideology. Artikel ini telah menganalisis proses panjang Pembentukan Negara Bangsa Indonesia, yaitu dari Masa Kolonial Belanda ke Era Orde Baru tahun 1980-an dan 1990-an. Artikel ini berpendapat bahwa konsep kebangsaan tetap sangat cair untuk waktu yang lama tetapi secara bertahap mulai terbentuk setelah pengenalan pendidikan barat untuk pribumi di era Kolonial Belanda dan mengambil bentuk akhir di Era Orde Baru. Kompleksitas pembentukan negara-bangsa adalah karena wilayah ini terdiri dari banyak suku, budaya, bahasa, agama, dan partai politik. Identitas nasional mereka dimulai dari kesadaran etnis yang terbentuk di Era Kolonial Belanda. Selama era pendudukan Jepang, formasi Negara Bangsa Indonesia dilaksanakan sebagai Kurasawa mengatakan bahwa mereka telah mempersiapkan kemerdekaan bangsa Indonesia. Di era Soekarno, Indonesia masih secara ideologis dibagi menjadi beberapa ideologi internasional seperti Komunisme, Islamisme, dan ideologi nasional sekuler. Puncak saingan adalah pecahnya pemberontakan Partai Komunis Indonesia pada tahun 1965. Perubahan besar terjadi dengan jatuhnya rejim Sukarno yang digantikan oleh Jenderal Suharto. Suharto menyebut era Soekarno sebagai rezim orde lama dan menyebut rejimnya sebagai Orde Baru. Stabilitas formasi Nasional Indonesia dipulihkan dengan larangan Ideologi Internasional seperti Komunisme, memaksa militansi Islam dan menggunakan Ideologi Nasional (Pancasila) sebagai Ideologi Nasional.